Symposium on health care ethics - Primeaux, Patrick; Pava, Moses L. (Emerald, 2000)
List of contributors. Statement of purpose. Editorial board. Responsibility, participation, and relationships: an introduction to the Symposium on Health Care Ethics (M.L. Pava). Healthcare management ethics: reflections on quality (L.J. Weber). Medical directors at the intersection of clinical and business ethics in managed care (M.E. Meaney). Ethical conflict in professionals: nurses' accounts of ethical conflict with organizations (A. Guadine, L. Thorne). Hospital mergers and the care of external stakeholders: a case study (R.E. Kidwell Jr.). Just distribution of rehabilitation resources for persons suffering from traumatic brain injury (M. Martone). Reclaiming the bedside: returning health care to the community (L.H. Newton). Organizational Ethics. Leadership in business and the ethical dilemma: a view through the eyes of the fish (E.F. Harshman, C.L. Harshman). Stoking the engine: the pressure release effect in management control (L. Brennan, G. Vega). Book Review. The literature of healthcare ethics (1997-1999) access and administration (G. Vega).
Keywords: Medical ethics -- Congresses.; elektronické knihy; electronic books